Assessing the feasibility of carbon tax implementation: Policy, economic, and administrative challenges - Yahya, Omar Deandra; Rosdiana, Haula (Energy Justice, 2025)
Background: This study aims to find and explain the feasibility of implementing a carbon tax in Indonesia. Carbon tax is a complex policy instrument because it includes aspects of taxation, environment, and scientific knowledge related to carbon emissions. Method:This study uses a qualitative approach through literature study and in-depth interviews to analyze the feasibility of a carbon tax based on the principles of good tax policy. Findings: Based on the analysis of four main aspects of tax policy—fairness, economic efficiency, administration, and coherence—carbon tax still faces obstacles in administrative implementation. The main challenges lie in the limited public knowledge of carbon tax and the unpreparedness of the administrative system in managing taxes that involve environmental and scientific factors. In addition, not all people have or use carbon tax objects, such as electricity, so its implementation can cause injustice. Conclusion: The implementation of a carbon tax can have negative impacts if not accompanied by adequate mitigation. One of them is the potential for an increase in the price of essential commodities, such as electricity tariffs, which can burden the community and industry. Therefore, community readiness, mitigation of economic impacts, and readiness of the administrative system and human resources are crucial factors before a carbon tax can be implemented effectively in Indonesia. Novelty/Originality of This Article: This study highlights the administrative challenges in implementing carbon tax in Indonesia with a focus on community readiness, economic impacts, and the integration of tax policy with environmental and scientific aspects, which have been rarely discussed before.